2012
DOI: 10.1021/jp3001306
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dynamics of a Noncovalent Charge Transfer Complex from Femtosecond Stimulated Raman Spectroscopy

Abstract: Femtosecond stimulated Raman spectroscopy is used to examine the structural dynamics of photoinduced charge transfer within a noncovalent electron acceptor/donor complex of pyromellitic dianhydride (PMDA, electron acceptor) and hexamethylbenzene (HMB, electron donor) in ethylacetate and acetonitrile. The evolution of the vibrational spectrum reveals the ultrafast structural changes that occur during the charge separation (Franck-Condon excited state complex → contact ion pair) and the subsequent charge recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…We consider the nature of this prompt charge-separated excitation-Coulomb-bound electron-hole pair versus unbound charges with correspondingly large separationby comparing to previous Raman studies on charge separation in solution as follows. In a previous FSRS study employed to follow the charge separation process of a non-covalent charge transfer complex in solution, Fujisawa et al 32 observed that the frequencies of Raman modes remained constant throughout the process, and concluded that the Franck-Condon state had significant charge-separated character, which is a very similar scenario as presented here. Earlier work by Vauthey et al 33 utilized time-resolved resonance-Raman spectroscopy with nanosecond resolution to follow the separation of a geminate ion pair into free ions in solution, and the authors distinguished between loosely bound charge pairs and separated ions invoking changes in the band frequencies.…”
Section: Discussionsupporting
confidence: 75%
“…We consider the nature of this prompt charge-separated excitation-Coulomb-bound electron-hole pair versus unbound charges with correspondingly large separationby comparing to previous Raman studies on charge separation in solution as follows. In a previous FSRS study employed to follow the charge separation process of a non-covalent charge transfer complex in solution, Fujisawa et al 32 observed that the frequencies of Raman modes remained constant throughout the process, and concluded that the Franck-Condon state had significant charge-separated character, which is a very similar scenario as presented here. Earlier work by Vauthey et al 33 utilized time-resolved resonance-Raman spectroscopy with nanosecond resolution to follow the separation of a geminate ion pair into free ions in solution, and the authors distinguished between loosely bound charge pairs and separated ions invoking changes in the band frequencies.…”
Section: Discussionsupporting
confidence: 75%
“…In the case of BUMA, the generated pulses have been reported to be self‐compressed to 30 to 60 fs . In most other cases, the probe pulses were compressed using either chirped mirrors or prism compressors (e.g …”
Section: Methodsmentioning
confidence: 99%
“…This produces the pulse sequence indicated in Figure and yields simultaneously the probe background, the ground‐ and excited‐state FSRS, and the transient absorption spectra . This scheme has been widely adapted for FSRS experiments with great success and simplifies data analysis, especially for molecules that show transient absorption or stimulated emission bands in the vicinity of the Raman probe . On the downside, both schemes lead to an overly excessive acquisition of the probe background (and transient‐absorption), which limits the time used for actually acquiring the excited state spectra to only 50 %.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of charges unequivocally proves that the 450-510 nm optical band corresponds to the charge transfer transition. However it should be noted that the absence of any rise time of the radical ion-pair state implies rare and unprecedented photochemistry of the nanoconfined host-guest CT complexes.In classical π-stacked CT complexes, the radical ion pair emerges via the short-lived photoexcited coupled CT state driven by slow structural rearrangements or solvent motions 30. The 9-AA⊂ EnPdcage complex showed the characteristic coupled CT band with a broad ESA feature that ranges from 850 nm to 1200 nm as shown inFigure 4c.This assignment is confirmed by comparing the observed ESA feature of 9-AA inclusion complexes from two different Pd 2+variants of the Pd 6 L 4 12+ cage i.e.…”
mentioning
confidence: 98%